The Effect Of Warm Ginger Compress On Reducing Gout Arthritis Pain In The Elderly - Musta’in Musta’in; Tri Yuniarti; Ikrima Rahmasari; Ellen Yolanda Cristin R; Saryadi Saryadi (International Journal of Medicine and Health, 2023)
Background: Gout arthritis (gout) is a disease that arises due to excessive blood uric acid levels, which causes excessive blood uric acid levels, namely the production of uric acid in the body more than its disposal, besides that the cause of excessive uric acid production in the body can occur due to genetic factors (congenital), food factors. Complaints of gout arthritis pain vary from mild, moderate to severe. One of the non-pharmacological therapies that can be used to relieve gout arthritis pain is warm ginger compresses. This study aims to see the effect of warm ginger compresses on the gout arthritis pain scale. Methods: This research is a type of pre-experimental research, namely experimental research without a control group. The research was conducted with a one group pre-posttest design. Sampling using total sampling technique. Results: The results of the Friedman test showed a P value (0.000). The results of this study indicate that warm ginger compresses can reduce gout arthritis pain. Conclusion: There is a significant effect on the level of gout arthritis pain before and after the warm ginger compress intervention